Indian summer monsoon variations during the Younger Dryas as revealed by a laminated stalagmite record from the Tibetan Plateau. (15th February 2022) - Li, Youwei; Pérez-Mejías, Carlos; Zhao, Jingyao; Li, Hanying; Zhang, Haiwei; Lu, Jiayu; Wang, Jian; Duan, Pengzhen; Dong, Xiyu; Wang, Haibo; Ning, Youfeng; Qian, Zhi; et al.
Abstract: High-resolution and precisely dated hydroclimate records in the southeastern Tibetan Plateau (TP) remain sparse beyond the Holocene, which hampers our ability to understand the hydroclimate variability in this important Indian summer monsoon (ISM) fringe area and its global teleconnection. Here we present 3-y resolution δ 18 O and δ 13 C records from a laminated stalagmite (RG-3) from Rige Cave in the southeastern TP, spanning the Younger Dryas (YD). The records allow us to precisely characterize the timing, structure, and particularly centennial-scale events within the YD, and probe the control factors of precipitation δ 18 O (δ 18 Op ) in the ISM fringe area. On centennial–millennial timescales, the Rige δ 18 O record shows coherent pattern with the East Asian summer monsoon (EASM) counterpart, combined with modeled δ 18 Op results and spatial analysis, suggesting that δ 18 Op in this part of the TP is largely controlled by the large-scale atmosphere circulation (or the ISM strength), and the altitude increase in the TP may not potentially result in an opposite δ 18 Op pattern at least in the monsoonal TP regime. We also found significant δ 13 C-δ 18 O covariation on the centennial timescale, suggesting a coincided ISM rainfall and biomass change during the YD. In the Rige records, one weak centennial-scale ISM event (namely the intra-Allerød cold period, IACP) and three strong centennial-scale ISM events within the YD (namely A1′-A2′-A3′) were prominent and occurred between ∼12, 470 and 12, 310 ± 14, ∼12, 210–12, 090 ± 12 and ∼12, 010–11, 920 ± 12 y BP (before present, where present = 1950 CE), respectively. Spectral analyses of Rige records also revealed a significant ∼200-y periodicity, which is nearly in-phase with observed centennial-scale variations of the North Atlantic temperature and mid-latitude westerly-jet during that time. These observations support the hypothesis that the solar de Vries cycle (207-y) triggered the centennial-scale climate variations in high northern latitude, leading to the ISM variations via fast atmospheric processes. Highlights: Precipitation δ 18 O and its millennial-centennial patterns in SE Tibet Plateau are controlled by large monsoon circulations Centennial δ 13 C-δ 18 O covariations in Younger Dryas suggest a link of the local biomass to Indian summer monsoon rainfall Centennial Indian summer monsoon events in Younger Dryas correlate precisely to the North Atlantic climate variations Solar de Vries cycle (207-y) triggered centennial Indian summer monsoon variations via North Atlantic climate changes